PENERAPAN MODEL COOPERATIVE LEARNING TYPE STUDENT TEAM ACHIEVEMENT DIVISION BERBANTUAN MEDIA SPINNING WHEEL TERHADAP HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 59 LUBUKLINGGAU - Tariihoran, Thomas Andrea; Charli, Leo; Hajani, Tri Juli (LP4MK STKIP PGRI Lubuklinggau, 2024)
This research aims to determine the completeness of social studies learning outcomes after implementing the Cooperative Learning Type Student Team Achievement Division model assisted by Spinning Wheel Media on the social studies learning outcomes of Class V Students at SD Negeri 59 Lubuklinggau. The research method used was an experiment with a one group test pretest-posttest research design. The population in this study were all fifth grade students at SDN 59 Lubuklinggau and at the same time the research sample consisted of 21 students. The data collection technique in this research uses a test in the form of multiple choice questions. Based on the results of data analysis with a significance level of a= 5%, it was obtained that Z count = -5.47 and Z table = 1.72 (Z count < Z table). Thus, it can be concluded that after the implementation of the Cooperative Learning Type Student Team Achievement Division model assisted by Spinning Wheel Media, it is significantly complete. Keywords: IPS, Spinning Wheel, Cooperative Learning Type Student Team Achievement Division model